Copayments in the German health system: does it work? - Boris Augurzky; Thomas K. Bauer; Sandra Schaffner (Institute for the Study of Labor (IZA), 2006)
This paper examines the effect of copayments on doctor visits using the German health care reform of 2004 as a natural experiment. In January 2004, copayments of 10 euros for the first doctor visit in each quarter have been introduced for all adults in the statutory health insurance. Individuals covered by private health insurance as well as youths have been exempted from these copayments. We use them as control groups in a difference-in-differences approach to identify the causal impact of these copayments on doctor visits. In contrast to expectations and public opinion our results indicate that there are no statistically significant effects of the copayments on the decision of visiting a doctor.
Keywords: 330